2012
DOI: 10.2147/ijn.s35279
|View full text |Cite
|
Sign up to set email alerts
|

Co-nanoencapsulation of magnetic nanoparticles and selol for breast tumor treatment: in vitro evaluation of cytotoxicity and magnetohyperthermia efficacy

Abstract: Antitumor activities have been described in selol, a hydrophobic mixture of molecules containing selenium in their structure, and also in maghemite magnetic nanoparticles (MNPs). Both selol and MNPs were co-encapsulated within poly(lactic-co-glycolic acid) (PLGA) nanocapsules for therapeutic purposes. The PLGA-nanocapsules loaded with MNPs and selol were labeled MSE-NC and characterized by transmission and scanning electron microscopy, electrophoretic mobility, photon correlation spectroscopy, presenting a mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, inorganic selenite is poorly selective for cancer cells and thus presents severe systemic toxicity, limiting its clinical application. Selol is a mixture of selenitetriacylglycerides that has low cumulative toxicity [8,9], whereas its anticancer activity has been associated with the production of oxygen reactive species, which eventually leads to irreversible cell damage, cell cycle arrest, and the sensitization of multidrug-resistant cells [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, inorganic selenite is poorly selective for cancer cells and thus presents severe systemic toxicity, limiting its clinical application. Selol is a mixture of selenitetriacylglycerides that has low cumulative toxicity [8,9], whereas its anticancer activity has been associated with the production of oxygen reactive species, which eventually leads to irreversible cell damage, cell cycle arrest, and the sensitization of multidrug-resistant cells [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In the other study, the effect of PLGA nanocapsules loaded with MNPs and selol treatment on the viability of the MCF-7 cell lines was tested with or without subsequent exposure to the external alternating magnetic field (AMF). The results showed that the presence of AMF caused a 50% decrease in cell viability [ 37 ]. Wang et al investigated the antitumor effect of a nanoparticle-based delivery system containing cross-linked hyaluronic acid and a low dose of DOX (X-NP-DOX) in both in vitro and in vivo conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Trx also plays an important role in cell viability and in the regulation of apoptosis in vitro [ 47 , 48 ]. Inactivation of TrxR-1 in mouse embryos disturbs cell proliferation, causing retardation of neural tube closure and consequently their death in utero [ 45 , 49 ]. Likewise, a mitochondrial redox protein Trx-2 is required for proper embryonic development and it is necessary for actively respiring cells.…”
Section: Selenium and Selenoproteins In Normal Brain Functionmentioning
confidence: 99%